말초신경 재건을 위한 인회석 박막 코팅 미세공성 신경재생관(nerve conduit)의 개발 - 이종호(Jong-Ho Lee); 황순정(Soon-Jeong Hwang); 최원재(Won-Jae Choi); 김성민(Soung-Min Kim); 김남열(Nam-Yeol Kim); 이은진; 안강민(Kang-Min Ahn); 명훈(Hoon-Myung); 서병무(Byoung-Moo Seo); 최진영(Jin-Young Choi); 정필훈(Pill-Hoon Choung); 김명진(Myung-Jin Kim); et al. (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2003)
KCI Citation Count: 0